Clinical features of pediatric eosinophilic gastroenteritis. Issue 1 (4th November 2022) - Kobayashi, Soya; Tsunoda, Tomoyuki; Umetsu, Shuichiro; Inui, Ayano; Fujisawa, Tomoo; Sogo, Tsuyoshi
Abstract: Background: No study has analyzed more than100 cases of eosinophilic gastroenteritis (EGE) in children in a single center. We aimed to describe the clinical features of pediatric EGE. Methods: This retrospective study was conducted at a single center. Between April 2007 and December 2017, 860 children between the ages of 1 year and 15 years underwent endoscopy for gastrointestinal symptoms of unknown cause. Among them, 109 (12.7%) were diagnosed with EGE according to the diagnostic criteria for EGE developed by the research group of the Ministry of Health, Labour and Welfare of Japan for eosinophilic gastrointestinal disorder in 2015. We investigated their symptoms, comorbidities, endoscopic findings, pathological findings, treatments, and outcomes. Results: Seventy‐one boys (65.1%) and 38 girls (34.9%) were diagnosed with EGE. The median age at diagnosis was 11 years (range, 1–15 years). The chief complaints were abdominal pain in 83 (76.1%) and diarrhea in 26 (23.9%). Upper and lower gastrointestinal endoscopies showed normal findings in 32 patients (29.4%). The most common treatment was a combination of elimination of foods suspected of causing EGE and anti‐allergic agents in 50 cases (45.9%). The outcomes were symptom disappearance in 43 patients (39.4%) and symptom improvement in 53 patients (48.6%). Conclusions: For gastrointestinal symptoms of unknown cause in children, EGE should be considered as a differential diagnosis. Although the symptoms and endoscopic findings are nonspecific, cracked mucosa may be a specific endoscopic finding for pediatric EGE. An elimination diet and/or anti‐allergic drugs were effective in most patients with pediatric EGE.